Different Patterns of Cerebral and Muscular Tissue Oxygenation 10 Years After Coarctation Repair - Vandekerckhove, Kristof; Panzer, Joseph; Coomans, Ilse; Moerman, Annelies; De Groote, Katya; De Wilde, Hans; Bové, Thierry; François, Katrien; De Wolf, Daniel; Boone, Jan (Frontiers in Physiology, 2019)
The purpose of this study was to assess whether the lower exercise tolerance in children after coarctation repair is associated with alterations in peripheral tissue oxygenation during exercise. 16 children after coarctation repair and 20 healthy control subjects performed an incremental ramp exercise test to exhaustion. Cerebral and locomotor muscle oxygenation were measured by means of Near Infrared Spectroscopy. The responses of cerebral and muscle tissue oxygenation index (cTOI, mTOI), oxygenated (O2Hb) and deoxygenated hemoglobin (HHb) as a function of work rate were compared. Correlations between residual continuous wave Doppler gradients at rest, arm-leg blood pressure difference and local oxygenation responses were evaluated. Age, length and weight was similar in both groups. Patients with aortic coarctation had lower peak power output (Ppeak) (72.3±20.2% vs. 106±18.7%, P<0.001), VO2peak/kg (37.3±9.1 vs. 44.2±7.6 ml/kg, P=0.019) and %VO2peak/kg (85.7±21.9% vs. 112.1±15.5%, P< 0.001). Cerebral O2Hb and HHb had a lower increase in patients vs. controls during exercise, with significant differences from 60 to 90%Ppeak (O2Hb) and 70% to 100%Ppeak (HHb). Muscle TOI was significantly lower in patients from 10 to 70%Ppeak and muscle HHb was significantly higher in patients vs. controls from 20 to 80%Ppeak. Muscle O2Hb was not different between both groups. There was a significant correlation between residual resting blood pressure gradient and Δmuscle HHb/ΔP at 10-20W and 20-30W (r=0.40, P=0.039 and r=0.43, P=0.034). Children after coarctation repair have different oxygenation responses at muscular and cerebral level. This reflects a different balance between O2 supply to O2 demand which might contribute to the reduced exercise tolerance in this patient population.